The father of her sons - Rimmer, Christine (Harlequin special edition, 2021)
How do you make up for four years of lost time? No last names. No promises to meet again. No way for Payton Dahl to find the man who's the father of her twin boys. Until fate reunites them four years later. Easton Wright now wants to be part of his sons' lives - with the woman he fell hard for during those seven days and nights of bliss. Payton doesn't want her sons to grow up fatherless like she did, but can she risk trusting Easton when she's been burned in the past?